Retrospective study of efficacy and adverse events of immune checkpoint inhibitors in 22 xeroderma pigmentosum patients with metastatic or unresectable cancers - Fernandez, Elvelyn R.; Tamura, Deborah; Khan, Sikandar G.; Momen, Sophie; Fassihi, Hiva; Sarkany, Robert; DiGiovanna, John J.; Kraemer, Kenneth H. (Frontiers in Oncology, 2023)
Deficient DNA repair in patients with the rare genetic disease, xeroderma pigmentosum (XP), results in a more than 1000-fold increased risk of sunlight induced skin cancers (basal cell carcinoma, squamous cell carcinoma and melanoma). Reduced DNA repair can lead to increased numbers of mutations in cancers and non-cancer tissues. These increased mutations may enhance the efficacy of immune checkpoint inhibitors (ICI) but might also lead to increased adverse events. In this retrospective study, we reviewed medical records and publications of ICI treated XP patients. We found that all 22 XP patients with metastatic melanoma or other unresectable cancers showed regression or remission. The XP patients experienced adverse events of similar types and frequencies as the ICI treated patients in the general population. However, 2 XP patients had additional cancers that did not respond to ICI, 2 XP patients had cancer recurrence or progression after initial response and 8 XP patients developed new skin cancers during or after ICI treatment. Immune checkpoint inhibitors can be considered in treating metastatic or unresectable cancers in XP patients.